2013
DOI: 10.1021/ja4107463
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Light Harvesting in the Green Alga Chlamydomonas reinhardtii: The C-Terminus of LHCSR Is the Knob of a Dimmer Switch

Abstract: Feedback mechanisms that dissipate excess photoexcitations in light-harvesting complexes (LHCs) are necessary to avoid detrimental oxidative stress in most photosynthetic eukaryotes. Here we demonstrate the unique ability of LHCSR, a stress-related LHC from the model organism Chlamydomonas reinhardtii, to sense pH variations, reversibly tuning its conformation from a light-harvesting state to a dissipative one. This conformational change is induced exclusively by the acidification of the environment, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
147
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(167 citation statements)
references
References 32 publications
17
147
1
2
Order By: Relevance
“…We have recently shown that this is not the case for isolated LHCII in the absence of aggregation from both plants and C. reinhardtii (18,26). Our results here show that LHCII in the membrane is not quenched in response to pH changes, and that the quenching can also not be induced by the interaction of zeaxanthin with LHCBM1.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…We have recently shown that this is not the case for isolated LHCII in the absence of aggregation from both plants and C. reinhardtii (18,26). Our results here show that LHCII in the membrane is not quenched in response to pH changes, and that the quenching can also not be induced by the interaction of zeaxanthin with LHCBM1.…”
Section: Discussionmentioning
confidence: 40%
“…The data clearly show that the membrane only acquires the ability to switch states in response to pH when LHCSR1 is present. Very little information is available about LHCSR1 of C. reinhardti;, however, this protein has a very high homology with LHCSR3 that was previously shown to assume a Q conformation at low pH by in vitro experiments, with a reduction in its fluorescence yield of ∼30% (17,18). LHCRS1 also retains the C-terminal tail that was shown to be essential in LHCSR3 for sensing the pH (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, three proteins have been shown to have a major role in detecting and transducing the low pH signal: the low pH activated violaxanthin de-epoxidase enzyme (VDE; Arnoux et al, 2009) that catalyses the conversion of the xanthophyll violaxanthin into zeaxanthin, a pigment involved in NPQ and other photoprotection mechanisms (Demmig-Adams, 1990;Havaux and Niyogi, 1999); the pigment-binding LhcSR proteins that belong to the Lhc family and are very likely the active site of quenching after protonation of C-terminal residues (Peers et al, 2009;Bonente et al, 2011;Liguori et al, 2013); and the PsbS protein that is protonated on two luminal Glu residues (Li et al, 2000;Li et al, 2004) and is proposed to subsequently promote the reorganization of the photosynthetic apparatus in order to create quenching sites elsewhere (Bassi and Caffarri, 2000;Bonente et al, 2008a;Johnson et al, 2011). It should be noted that efficient energy quenching also requires the presence of Lhc proteins, but this does not require a specific Lhc isoform (Andersson et al, 2001(Andersson et al, , 2003de Bianchi et al, 2008de Bianchi et al, , 2011.…”
mentioning
confidence: 99%
“…LhcSR3 is homologous to the Lhc proteins: it has a similar structure with three transmembrane helices and it is also able to bind Chls and Cars (Bonente et al, 2011). It has been suggested that LhcSR3 itself is the energy quencher due to its pigment binding ability, the unusual fluorescence properties that show very short lifetime components, and its pH sensitivity (Bonente et al, 2011;Liguori et al, 2013;Tokutsu and Minagawa, 2013). A recent investigation suggests the LhcSR is localized both in grana membranes and stroma lamellae in the moss Physcomitrella patens (Pinnola et al, 2015), and investigations on Chlamydomonas suggest that LhcSR3 can bind both to PSI or PSII depending on illumination conditions (Allorent et al, 2013;Bergner et al, 2015).…”
mentioning
confidence: 99%